Manajemen Kinerja Pengelolaan Arsip Statis di Unit Pusat Arsip Universitas Negeri Malang pada Masa Pandemi Covid-19 - Meirisa Anggraeni; Imam Suyitno; Andi Asari (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Static archives are types of archives that have historical value for the institution that created the archive, and the information contained in the archive supports the sustainable development activities of an institution. Therefore, effective management implementation is needed. Performance management is one of the processes conducted in order to be able to complete the archiving activities efficiently and effectively. This study aims to describe performance management in managing archives during the Covid-19 pandemic. The methodology used in this study is qualitative descriptive. This study is built upon Michael Armstrong’s performance management model to specifically describe the planning to performance evaluation stages. The results show that the performance archive management is carried out by following the rules and performance lines that have been set by adjusting the conditions of the Covid-19 pandemic. This can be seen from (1) the planning stage under the virtual implementation processes in accordance to applicable bureaucratic rules and the production of several reference documents, (2) implementation stage where archivists carried out management in a flexi-time manner by referring to the performance plan, (3) performance monitoring that is carried out through the staffing system, and (4) internal evaluation that is done in the archive center unit as well as by the relevant institution Keywords: performance management, static archives, Covid-19 pandemic period Abstrak: Arsip statis merupakan jenis arsip yang memiliki nilai guna kesejarahan bagi lembaga pencipta arsip. Serta informasi yang terkandung dalam suatu arsip dapat menunjang kegiatan pengembangan berkelanjutan. Oleh karena itu, penerapan manajemen yang efektif sangat dibutuhkan. Manajemen kinerja adalah salah satu proses untuk membuat aktivitas diselesaikan secara efisien dan efektif. Penelitian ini bertujuan mendeskripsikan manajemen kinerja dalam pengelolaan arsip statis di masa pandemi covid-19. Metodologi yang digunakan adalah rancangan penelitian kualitatif-deskriptif. Penelitian ini mengusung model manajemen kinerja Michael Armstrong dengan memaparkan tahap perencanaan sampai dengan evaluasi pengelolaan. Serta hasil penelitian menunjukkan bahwa manajemen kinerja pengelolaan arsip statis terlaksana mengikuti aturan dan alur kinerja yang telah ditetapkan dengan menyesuaikan kondisi pandemi Covid-19. Hal ini terlihat melalui (1) tahap perencanaan, dilaksanakan secara virtual dan dilakukan sesuai aturan birokrasi yang berlaku dan menghasilkan beberapa dokumen acuan, (2) pelaksanaan, arsiparis melaksanakan pengelolaan secara flexi-time dengan mengacu pada rencana kinerja, (3) pengawasan dilakukan melalui sistem kepegawaian, dan (4) terdapat evaluasi internal unit kerja pusat arsip dan evaluasi lembaga yang menaungi. Kata kunci: manajemen kinerja, pengelolaan arsip statis, masa pandemi Covid-19